Synergistic Activity of Tetrandrine and Colistin against mcr-1-Harboring Escherichia coli - Muhammad Shafiq; Fen Yao; Hazrat Bilal; Sadeeq Ur Rahman; Mi Zeng; Ilyas Ali; Yuebin Zeng; Xin Li; Yumeng Yuan; Xiaoyang Jiao (MDPI AG, 2022)
Before the emergence of plasmid-mediated colistin resistance, colistin was once considered the last drug of choice for infections caused by carbapenem-resistant bacteria. Currently, researchers are relentlessly exploring possible alternative therapies that could efficiently curb the spread of drug resistance. In this study, we aim to investigate the synergistic antibacterial activity of tetrandrine in combination with colistin against mcr-1-harboring Escherichia coli. We examined the antibacterial activity of tetrandrine in combination with colistin in vivo and in vitro and examined the bacterial cells by fluorescence, scanning, and transmission electron microscopy (TEM) to explore their underlying mechanism of action. We further performed a computational analysis of MCR-1 protein and tetrandrine to determine the interaction interface of these two molecules. We confirmed that neither colistin nor tetrandrine could, on their own, inhibit the growth of mcr-1-positive E. coli. However, in combination, tetrandrine synergistically enhanced colistin activity to inhibit the growth of E. coli both in vivo and in vitro. Similarly, molecular docking showed that tetrandrine interacted with the three crucial amino acids of the MCR-1 protein in the active site, which might inhibit MCR-1 from binding to its substrates, cause MCR-1 to lose its ability to confer resistance. This study confirmed that tetrandrine and colistin have the ability to synergistically overcome the issue of colistin resistance in mcr-1-harboring E. coli.